INVERSE AGONISTS: MORE THAN JUST ANTAGONISTS? - R. N. Alyautdin; B. K. Romanov (Безопасность и риск фармакотерапии, 2022)
This review presents information on pharmaceuticals that have the properties of inverse agonists. The article describes the features of the interaction of the ligand - receptor with constitutive conformational changes. Many of ligands, assumed to be neutral antagonists, behave as inverse agonists displaying negative efficacy in experimental systems. This suggests that their therapeutic actions may involve not only receptor blockade, but also the decrease of spontaneous receptor activity. Examples of inverse agonists that influence the processes of excitation of adrenergic, histaminergic, opioid and benzodiazepine receptors are presented. The existence of constitutive activity in vivo and its pathophysiological relevance are also discussed